A conceptual model for evaluating product-service systems leanness in UK manufacturing companies - Elnadi, M.; Shehab, Essam (Elsevier, 2014)
The purpose of this paper is to present a conceptual model that can be used in measuring the degree of Product-Service System (PSS) leanness in UK manufacturing companies. The model will assess Product-Service System leanness based on five lean enablers (supplier relationship, management leanness, workforce leanness, process excellence, and customer relationship), 21 criteria (supplier delivery, culture of management, process optimisation, etc.) and finally 73 attributes. This proposed model will be the base of developing an index used as quantitative measure of the degree of Product-Service System leanness in manufacturing companies.
Keywords: Leanness; PSS; Conceptual model